Electric Seeing : Positions in Contemporary Video Art - Klink, Charlotte (Image (Transcript (Firm)), 2022)
What is the subject of video? Charlotte Klink traces the development of electromagnetism in the pursuit of "Electric Seeing" that emerged in the 19th century as well as its curious relation to psychoanalysis and the contemporary discovery of the structure of the human psyche. In doing so, she exposes how this development laid the foundation of what we know today as "video". This comprehensive theory of video entails a discussion of the technological, historical, and etymological roots, the media-theoretical concepts of medium and index, the philosophical and art-theoretical environment in which video emerged in the 1960s, the psychoanalytic concept of the phantasm, and artworks by artists such as Yael Bartana and Hito Steyerl, and Bjørn Melhus.